The new Ayn Rand companion - Gladstein, Mimi Reisel; Gladstein, Mimi Reisel (Westport, Connecticut Greenwood Press, 1999)
Essential guide to the life and works of Ayn Rand, the book chronicles and summarizes her writings, presents information about her national and global impact--and the response to it. New materials about Rand's posthumous publications, the latest biographical information, and summaries of books and articles about Rand, published since her death, have been included in this new edition.
Acknowledgments -- Introduction -- Biographical data -- The fiction -- A compendium of characters -- The nonfiction -- Criticism of Rand's works -- Appendix -- Bibliography -- Index.
Rev. ed. of: The Ayn Rand companion. 1984.
Keywords: Rand, Ayn -- Criticism and interpretation; Women and literature -- United States -- History -- 20th century; Philosophy in literature; Objectivism (Philosophy); Electronic books